A Patient-Derived iPSC-Based Model Reveals Neural Lineage-Specific Transcription of Endogenous HHV-6B - Hiroki Miura; Tomoki Inagaki; Tamae Ohye; Akiko Yoshikawa; Takayuki Murata; Naoki Yahata; Yoshiki Kawamura; Yotaro Kondo; Jun-ichi Kawada; Masaru Ihira; Yuki Higashimoto; Yoshitaka Sato; et al. (The Journal of Infectious Diseases, 2026)
Abstract Background Endogenous human herpesvirus 6 (eHHV-6), in which the entire viral genome is integrated into human chromosomes, is present in approximately 1% of the population and has been associated with various clinical conditions, including neurological disorders. However, its biological significance remains unclear due to the lack of appropriate experimental models. Methods We established a patient-derived induced pluripotent stem cell (iPSC)–based tissue culture model using lymphoblastoid cell lines from individuals with eHHV-6B. iPSCs retaining the integrated viral genome were generated and subsequently differentiated into neural stem cells (NSCs). Viral gene expression was evaluated by RT-qPCR under basal conditions and following chemical stimulation. Results The integrated HHV-6B genome was transcriptionally silent in iPSCs but exhibited spontaneous low-level expression of the immediate-early gene U90 and the late gene U100 in NSCs. Chemical stimulation further enhanced U90 expression, whereas induction of U100 did not reach statistical significance. These findings indicate preferential activation of early viral transcriptional programs in neural lineage cells. Conclusions Neural lineage cells provide a permissive environment for expression of eHHV-6B transcripts. This patient-derived iPSC-based model provides a platform for investigating the biological significance of neural lineage-specific eHHV-6 transcripts and may facilitate interpretation of HHV-6 DNA detection in patients with eHHV-6 by enabling studies of cell type-dependent viral transcription.